Roitt's essential immunology - Delves, Peter J.; Roitt, Ivan M. (Ivan Maurice).; ebrary, Inc. (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2011)
"A new, 12th edition of the definitive Immunology textbook, now fully up-to-date on the latest knowledge and concepts about the workings of the immune system. Essential Immunology is a perfect course textbook to support a series of lectures, or themes, on Immunology: pedagogy has been strengthened throughout, and the text is now fully supported by a suite of online resources as well as a FREE enhanced Wiley Desktop Edition"--Provided by publisher.
Machine generated contents note: Preface. -- Acknowledgements. -- 1. Innate Immunity. -- 2. Specific acquired immunity. -- 3. Antibodies. -- 4. Membrane receptors for antigen. -- 5. The primary interaction with antigen. -- 6. Immunological methods and applications. -- 7. The anatomy of the immune response. -- 8. Lymphocyte activation. -- 9. The production of effectors. -- 10. Control mechanisms. -- 11. Ontogeny and phylogeny. -- 12. Adversarial strategies during infection. -- 13. Vaccines. -- 14. Immunodeficiency. -- 15. Hypersensitivity. -- 16. Transplantation. -- 17. Tumour immunology. -- 18. Autoimmune diseases.
Rev. ed. of: Roitt's essential immunology / Ivan M. Roitt, Peter J. Delves.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Immunology; Electronic books